2019
DOI: 10.26905/jkdp.v23i4.3439
|View full text |Cite
|
Sign up to set email alerts
|

Women on boards and earnings management: What really matters?

Abstract: The diversity of gender and income conservatism has been intriguing topics over the last decade. The effect of women who are more likely to be financially conservative than men will bring impact on the practices of conservative accounting, particularly when determining revenues for corporate governance. Therefore, we investigate the effects of women leaders in corporate business and their impacts on earnings management. The population of the study includes companies indexed in the Indonesia Stock Exchange, exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
2
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 30 publications
2
24
2
2
Order By: Relevance
“…The results of this study are supported by research conducted by Ye et al (2010), who also found that the gender of the management board did not affect corporate earnings management. The results of this study contradict the research conducted by Kim et al (2017), Hala (2019), Harakeh et al (2019), who found that females in the management board negatively affected earnings management.…”
Section: Female In the Board Of Directors And Earnings Managementcontrasting
confidence: 99%
See 4 more Smart Citations
“…The results of this study are supported by research conducted by Ye et al (2010), who also found that the gender of the management board did not affect corporate earnings management. The results of this study contradict the research conducted by Kim et al (2017), Hala (2019), Harakeh et al (2019), who found that females in the management board negatively affected earnings management.…”
Section: Female In the Board Of Directors And Earnings Managementcontrasting
confidence: 99%
“…The presence of women in firm leaders also indicates the existence of gender diversity in firm leaders that can prevent specific individuals or groups from dominating the decision-making process (Lakhal et al, 2015). This is also supported by research conducted by Hala (2019) and Harakeh et al (2019), who found that women in upper management can reduce earnings management. Kim et al (2017) also found that female in management board had a negative effect on earnings management H 2 : More female presence on the board of directors has…”
Section: Female In Board Of Directors and Earnings Managementmentioning
confidence: 75%
See 3 more Smart Citations